Impact of American Political Marketing on Israeli Society. Issue 1 (2nd January 2017) - Scheindlin, Dahlia
Abstract : The extensive literature examining the impact of American campaign styles in other countries generally attributes various political changes to the presence of American professionals and imported campaign techniques. Yet foreign professionals working on international campaigns may have more or less influence, and there is little systematic understanding of the factors that contribute to their actual influence over the local campaign. This paper examines the Israeli case as an example of strong penetration of American campaign professionals and techniques and analyzes the factors that contributed to their relatively high level of influence. Following this, a framework is proposed for assessing when imported American professionals and/or styles are likely to have a strong or weak influence on a campaign, based on factors leading to easy adoption or requiring more extensive adaptation. The study finds that in Israel, endogenous factors including social, political, cultural, and economic evolution contributed to the easy adoption of American campaign practices, creating a welcoming environment for American professionals. Thus, the major changes in campaigns often attributed to Americanization in other countries may be due at least in part to organic social, economic, and cultural changes of that society.